Informal allies on a common mission: the Serbian state and the orthodox church in recent nation-building processes - Jovanović, Vladan (Journal for the study of religions and ideologies, 2018)
With the aim of exploring in detail Serbia's modern nation-building, this paper reveals and examines three stages in the relationship between the state and the Church. Their interaction was first observed in the late-1980s, when the Church leadership began to interfere in the state affairs, offering religious solutions to a wide range of national issues. Following the collapse of Serbian society during the 1990s, the Church has become an ideology supplement to the state-driven national project. As such, the Church was embraced by the state authorities, and after the fall of Miloevic in 2000, nationalism continued to exponentially increase in Serbia. Following the assassination of the Prime Minister Zoran Ðindic in 2003, the Church emerged as the key factor of nation building, thus substituting the disoriented state structures. A significant part of our conclusions are based on primary quantitative sources.